Gravity Predictions of International Migration Flows - Jesús Fernández-Huertas Moraga; Gonzalo López Molina (Institute of Labor Economics (IZA), 2024)
What is the future of international migration flows? The growing availability of bilateral international migration data has resulted in an improved understanding of the determinants of migration flows through the estimation of theory-based gravity models. However, the use of these models as a prediction tool has remained a mostly unexplored research area. This paper estimates simple gravity models of bilateral migration flows for the whole world and projects these models into the future. Our results confirm a limited role for economic factors and a large one for demographic ones, in line with the literature. As a novel contribution, we show that estimates based on net flows are substantially lower than those based on gross flows. The reason is that network effects are historically more correlated with gross than with net flows.
Keywords: F22; J11; J61; O15; 330; international migration; prediction; gravity model